Analyzing Hepatotoxicity: A Comparative Study of Simvastatin and Rosuvastatin, and Their Reversal Using Montelukast and Coenzyme Q10 (Medical Forum Monthly, 2023)
Objective: The study aims to compare the hepatotoxic potential simvastatin and rosuvastatin owing to the lack in knowledge regarding the comparative hepatotoxic potential of the two very commonly prescribed statins. In addition, the study also aims to assess the hepatoprotective efficacy of two other compounds, montelukast and coenzyme Q10.Study Design: Experimental study.Place and Duration of Study: This study was conducted at Pharmacology Dept, Animal house Northwest School of Medicine Hayatabad from 15th Jan 2023 to 10th July 2023.Methods: An experimental study was carried out in northwest school of medicine from 15th Jan 2023 to 10th July 2023 on 35 mice, randomly divided into 7 groups of 5 mice each. Group 1 served as a control group. Simvastatin 50mg/kg/day was administered intraperitoneally (I/P) to Group 2. Rosuvastatin I/P 50mg/kg/day was given to group 3. Simvastatin 50 mg/kg/day I/P and 3 mg/kg of montelukast were given to group 4. Rosuvastatin 50 mg/kg/day plus 3 mg/kg of Montelukast were given to group 5. Simvastatin 50 mg/kg/day and 10 mg/kg coenzyme Q10 were given to group 6. Group 7 received rosuvastatin 50 mg/kg/day plus 10 mg/kg I/P of coenzyme Q10.Results: Both statins demonstrated liver damage, although Rosuvastatin had more abnormalities in liver function. In the simvastatin group, montelukast did attenuate hepatotoxicity and induce regenerative changes. Instead of substantial liver function abnormalities, coenzyme Q10 did not demonstrate any protection against statins.Conclusion: Rosuvastatin had a higher hepatotoxic potential compared to simvastatin, as evidenced by the elevated liver enzymes and histological changes in the liver tissue. However, the study also found that montelukast showed a better hepatoprotective effect compared to coenzyme Q10, as it was able to effectively reverse the liver damage caused by both simvastatin and rosuvastatin.